Razer / Muhammad Arif Izzudin Ismail - Ismail, Muhammad Arif Izzudin (2022)
Many of Razer's products are focused towards gamers, including gaming laptops, cellphones, and PC accessories such as mice, audio players, keyboards, mouse pads, and gaming chairs. Razer also released Razer Comms, a VOIP application. The Razer Death Adder gaming mouse is the company's most popular product in terms of sales volume. Razer mice are used by about 5% of professional gamers. Snakes (mice), insects (mouse mats), arachnids (keyboards), marine animals (audio), and felines (audio) are all named after predatory or poisonous species (console peripherals). The sole exceptions are the Razer Blade and Razer Edge laptops, which are named after bladed things. Razer launched its first gaming device, the Razer Phone, in November 2017, marking the company's first entrance into the smartphone industry. Manufacturing costs were also a danger to Razer Inc. since they were constantly shifting and unpredictable. As a result, Razer will need to plan for instances where costs may surge. Precautionary planning results in manufacturing delays, which may harm Razer, Next, and the availability of substitute items. The aim of Razer to raise prices is limited by the availability of replacement choices, since customers may easily switch to another product or service. This will have a significant impact on Razer, since it will need to master this facet of quality.